2012
DOI: 10.5858/arpa.2010-0505-rs
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Meningioma

Abstract: Cutaneous meningioma is a rare tumor that most commonly occurs on the scalp and occurs in both congenital and acquired forms. It invokes a wide clinical differential diagnosis, but diagnosis is based on characteristic histologic and cytologic findings. Congenital lesions can often present years after birth and even in adult patients. Acquired lesions occur in adulthood. We review histologic, cytologic, and electron microscopic findings and explore how these are used to separate this entity from other entities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
66
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(66 citation statements)
references
References 28 publications
0
66
0
Order By: Relevance
“…Therefore, they should be included in the differential diagnosis when evaluating FNA material from tumors in this anatomical site. Cutaneous meningioma most commonly occurs on the scalp and may be congenital (ectopic) or acquired (representing a secondary extension from an underlying intracranial meningioma) [29]. Our patient (case 4) with multiple scalp lesions had a prior brain meningioma.…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, they should be included in the differential diagnosis when evaluating FNA material from tumors in this anatomical site. Cutaneous meningioma most commonly occurs on the scalp and may be congenital (ectopic) or acquired (representing a secondary extension from an underlying intracranial meningioma) [29]. Our patient (case 4) with multiple scalp lesions had a prior brain meningioma.…”
Section: Discussionmentioning
confidence: 93%
“…Because meningiomas are rare tumors associated with vague clinical features, they may have to be differentiated from lesions such as appendageal cell tumors, epithelioid/spindle cell sarcoma, peripheral nerve sheath tumors, squamous cell carcinoma, hemangioma, giant cell fibroblastoma, hemagiopericytoma, or other types of heterotopic neuroglial lesions. [2345] FNAC is a simple and effective procedure and can be highly valuable in diagnosis of cutaneous meningioma, as done in the present case.…”
Section: Discussionmentioning
confidence: 61%
“…However, if the lesion is small and asymptomatic, simple surgical excision can be considered. [25] In our case, the lesion was completely excised and sent for histopathological confirmation. Some studies found that cutaneous meningioma Type I has better prognosis.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…They are generally considered benign, particularly if classified as WHO grade I 1. Despite the first reported case in the English literature being in 1956, cutaneous meningioma remains a relatively rare tumour 2. Lopez et al 3 classify cutaneous meningiomas into three types: primary cutaneous meningiomas (type I), which are generally congenital; cutaneous extensions of extracranial soft tissue meningiomas (type II); and cutaneous meningiomas arising from an extension of a neuraxis meningioma to the skin (type III).…”
Section: Introductionmentioning
confidence: 99%